Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12929-016-0250-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing, virulence traits and antimicrobial resistance of diabetic foot staphylococci

Abstract: BackgroundDiabetes mellitus is a major chronic disease that continues to increase significantly. One of the most important and costly complications of diabetes are foot infections that may be colonized by pathogenic and antimicrobial resistant bacteria, harboring several virulence factors, that could impair its successful treatment. Staphylococcus aureus is one of the most prevalent isolate in diabetic foot infections, together with aerobes and anaerobes.MethodsIn this study, conducted in the Lisbon area, stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 61 publications
(63 reference statements)
4
63
3
1
Order By: Relevance
“…Two surface components have been implicated in biofilm formation by S. aureus, the product of the icaADBC operon and the Bap [42]. Our data were in agreement with previous studies, which have demonstrated that biofilm genes icaA/icaC/icaD were present in all isolates, whereas bap was always missing [43,44]. The relatively low detection rate of bap indicates that the ica-dependent mechanism might be primarily responsible for adhesion and biofilm production in S. aureus strains [45].…”
Section: Discussionsupporting
confidence: 91%
“…Two surface components have been implicated in biofilm formation by S. aureus, the product of the icaADBC operon and the Bap [42]. Our data were in agreement with previous studies, which have demonstrated that biofilm genes icaA/icaC/icaD were present in all isolates, whereas bap was always missing [43,44]. The relatively low detection rate of bap indicates that the ica-dependent mechanism might be primarily responsible for adhesion and biofilm production in S. aureus strains [45].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we used the biofilm-producing DFI strains Staphylococcus aureus Z25.2 and Pseudomonas aeruginosa Z25.1, co-isolated from a diabetic foot ulcer. The strains were selected from a bacterial collection obtained from patients with Diabetes mellitus and infected foot ulcers, as described in a previous study by Mendes et al [6] and characterized by Mottola et al [64]. All isolates were stored at -80 • C in buffered peptone water supplemented with 20% (v/v) of glycerol.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…Both were mainly manifested in more severe infections in grades III and IV and the results were stastically significant. tst gene was detected in only one isolate from diabetic foot ulcer (2.4%) in Mottola et al study [34].…”
Section: Discussionmentioning
confidence: 88%
“…coa and clfA genes were positive in 33 (97.1%) and 32 (94.1%) isolates respectively with nearly similar prevalence in all studied grades of diabetic foot infections. Mottola et al [34] found that all isolates were coa positive but only 70% were clfA positive.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation